Mathematical model of GTE working process for calculation of their emission characteristics - Запорожец, А. И.; Чумак, О. И.; Якушенко, А. С.; Охмакевич, В. Н. (Proceedings of National Aviation University (archive), 2000)
Considered are the methods of getting aviation gas-turbine engine emission characteristics. Described is the method of a numerical experiment allowing to take into account the influence of production, technological and performance factors on the emission characteristics of the engine. Presented are the achieved experiment results of the emission characteristics of the engine ПС-90А